Development and effectiveness of short video tutorials in basic turning learning to enhance students' cognitive ability - Prasetyo, Muhamad Julianes; Rifelino, Rifelino; Fauza, Anna Niska (Researcher and Lecturer Society, 2024)
This study aims to develop and evaluate the effectiveness of short tutorial videos in teaching the essential operation of lathe machines in mechanical engineering. Utilizing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the research was conducted at SMK N 1 Sumatera Barat, involving 65 vocational school students. The short tutorial videos were designed to enhance students' comprehension and cognitive ability in lathe machine operations, addressing the challenges posed by traditional teaching methods. Data were collected through questionnaires and practical tests to assess students' understanding and skills. The findings revealed that the short tutorial videos significantly improved students' comprehension and cognitive ability, although variations in understanding levels were observed. Normality tests confirmed a normal data distribution, allowing for the use of paired sample t-tests, which indicated no significant difference between the Mechanical Engineering and Industrial Mechanical Engineering groups after using the tutorials. Validation by media and content experts demonstrated the high quality and relevance of the instructional material. This study underscores the importance of developing more interactive and adaptive learning media and highlights the need to explore further other factors influencing cognitive ability.